GENIPIN-CROSSLINKED FIBRIN HYDROGELS AS A POTENTIAL ADHESIVE TO AUGMENT INTERVERTEBRAL DISC ANNULUS REPAIR - Schek, R.M. (2011)
Treatment of damaged intervertebral discs is a significant clinical problem and, despite advances in the repair and replacement of the nucleus pulposus, there are few effective strategies to restore defects in the annulus fibrosus. An annular repair material should meet three specifications: have a modulus similar to the native annulus tissue, support the growth of disc cells, and maintain adhesion to tissue under physiological strain levels. We hypothesized that a genipin crosslinked fibrin gel could meet these requirements. Our mechanical results showed that genipin crosslinked fibrin gels could be created with a modulus in the range of native annular tissue. We also demonstrated that this material is compatible with the in vitro growth of human disc cells, when genipin:fibrin ratios were 0.25:1 or less, although cell proliferation was slower and cell morphology more rounded than for fibrin alone. Finally, lap tests were performed to evaluate adhesion between fibrin gels and pieces of annular tissue. Specimens created without genipin had poor handling properties and readily delaminated, while genipin crosslinked fibrin gels remained adhered to the tissue pieces at strains exceeding physiological levels and failed at 15–30%. This study demonstrated that genipin crosslinked fibrin gels show promise as a gap-filling adhesive biomaterial with tunable material properties, yet the slow cell proliferation suggests this biomaterial may be best suited as a sealant for small annulus fibrosus defects or as an adhesive to augment large annulus repairs. Future studies will evaluate degradation rate, fatigue behaviors, and long-term biocompatibility.